The Norton anthology of English literature : volume 2 / Stephen Greenblatt, general editor ; M.H. Abrams, founding editor emeritus. - Greenblatt, Stephen, 1943-; Abrams, M. H. (Meyer Howard), 1912-2015 (W.W. Norton, 2006)
A survey of English literature from the Middle Ages to the twenty-first century, this edition represents essential works in genres, ranging from Seamus Heaney's translation of "Beowulf" to global twentieth-century classics. It contains concise glosses and annotations, period introductions, biographical headnotes, timelines and bibliographies.